2020
DOI: 10.3390/polym13010031
|View full text |Cite
|
Sign up to set email alerts
|

Amphiphilic Molecular Brushes with Regular Polydimethylsiloxane Backbone and Poly-2-isopropyl-2-oxazoline Side Chains. 2. Self-Organization in Aqueous Solutions on Heating

Abstract: The behavior of amphiphilic molecular brushes in aqueous solutions on heating was studied by light scattering and turbidimetry. The main chain of the graft copolymers was polydimethylsiloxane, and the side chains were thermosensitive poly-2-isopropyl-2-oxazoline. The studied samples differed in the length of the grafted chains (polymerization degrees were 14 and 30) and, accordingly, in the molar fraction of the hydrophobic backbone. The grafting density of both samples was 0.6. At low temperatures, macromolec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 87 publications
0
10
0
Order By: Relevance
“…In order to estimate the aggregation degree m agg for large aggregates, one can use the previously proposed approach [ 52 ] based on comparing the translational friction coefficients for macromolecules and aggregates. By modeling unimolecular micelles by spheres, and large aggregates by ellipsoids of revolution, it is possible to show that the aggregation degree associated with the parameters of the ellipsoid by the equation [ 52 ]: m agg = V ell / V sph = p 2 R f 3 /8 a 3 where V ell is the volume of the modeling ellipsoid of revolution, V sph is the volume of the modeling sphere, p = a / b , a and b are the major and minor axes of ellipsoid. Herein, the dependences of a and b on p for a model ellipsoid of revolution with a translational friction coefficient f are described by the formulas a = f /(6πη 0 F ( p )) b = f /(6πη 0 pF ( p )) where aF ( p ) = ( p 2 −1) 1/2 /( p ln(( p + ( p 2 −1) 1/2 )/( p −( p 2 −1) 1/2 )) …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to estimate the aggregation degree m agg for large aggregates, one can use the previously proposed approach [ 52 ] based on comparing the translational friction coefficients for macromolecules and aggregates. By modeling unimolecular micelles by spheres, and large aggregates by ellipsoids of revolution, it is possible to show that the aggregation degree associated with the parameters of the ellipsoid by the equation [ 52 ]: m agg = V ell / V sph = p 2 R f 3 /8 a 3 where V ell is the volume of the modeling ellipsoid of revolution, V sph is the volume of the modeling sphere, p = a / b , a and b are the major and minor axes of ellipsoid. Herein, the dependences of a and b on p for a model ellipsoid of revolution with a translational friction coefficient f are described by the formulas a = f /(6πη 0 F ( p )) b = f /(6πη 0 pF ( p )) where aF ( p ) = ( p 2 −1) 1/2 /( p ln(( p + ( p 2 −1) 1/2 )/( p −( p 2 −1) 1/2 )) …”
Section: Resultsmentioning
confidence: 99%
“…In order to estimate the aggregation degree m agg for large aggregates, one can use the previously proposed approach [52] based on comparing the translational friction coefficients for macromolecules and aggregates. By modeling unimolecular micelles by spheres, and large aggregates by ellipsoids of revolution, it is possible to show that the aggregation degree associated with the parameters of the ellipsoid by the equation [52]:…”
Section: Behavior Of Star-shaped Six-arm Pseudo-polypeptoids In Aqueous Solutions At Low Temperaturesmentioning
confidence: 99%
“…Our previous works described the synthesis, characterization, and conformational behavior of amphiphilic PDMSk- graft -PiPrOx molecular brushes with polydimethylsiloxane (PDMS) backbone and poly-2-isopropyl-2-oxazoline (PiPrOx) side chains, and the effect of PiPrOx side chain length on self-organization and aggregation in aqueous solutions was also investigated [ 42 , 43 ]. It was shown that the LCST for PDMSk- graft -PiPrOx with long side chains is higher than the LCST for samples with short PiPrOx chains, despite the fact that the M of the latter is almost two times lower.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the architecture parameters of grafted copolymers strongly affect the solubility and the assembly behavior of macromolecules compared to linear diphilic block-copolymers [ 7 , 8 , 9 , 10 ]. For example, the shape of the molecules of dense amphiphilic brushes in a thermodynamically poor solvent for the backbone resembles a star-shaped molecule, the core of which is a collapsed main chain, and the grafted chains are arms [ 11 , 12 , 13 , 14 ] A decrease in the grafting density of the side chains leads to a decline in solubility and to aggregate formation due to the interaction of insoluble components [ 15 , 16 ]. In particular, diphilic molecular brushes are able to form ordered micellar structures by the self-assembly processes of macromolecules in selective solvents.…”
Section: Introductionmentioning
confidence: 99%
“…A large number of works are devoted to the analysis of the stimulus sensitivity of molecular brushes [ 12 , 13 , 17 ]. However, the number of systematic studies of the concrete classes of polymer brushes is not very large.…”
Section: Introductionmentioning
confidence: 99%